Theoretical and Numerical Investigation of Required Torque in ECAP-Conform Process - Ghaforian Nosrati, Hasan; Khalili, Khalil; Gerdooei, Mahdi (Metallurgical and materials transactions. B, Process metallurgy and materials processing science, 2020)
In recent years, special attention has been paid to continuous methods of severe plastic deformation, such as the ECAP-Conform process. In this research, a new analytical method has been presented to calculate the required torque in ECAP-Conform of grade 2 commercially pure titanium (CP-Ti Gr. 2). In this regard, the process was divided into two regions, mainly the primary roll bending and the secondary ECAP zones. The energy balance method, as well as the upper-bound analysis, was used to calculate the required force and torque in the first and the second regions, respectively. Also, the ABAQUS/Explicit solver was utilized to simulate the ECAP-Conform process, as well as the numerical results, were compared with the theoretical outcomes. The shear friction factor between the die and the CP-Ti rod was estimated by the ring compression test for different lubricating conditions. It was found that whereas the friction factor plays an essential role in the implementation of the process, the hardening exponent of the raw material has a negligible effect on the required torque. Furthermore, in ECAP-Conform of AA6061 rod, the required torque for different die channel angles was calculated and compared with other researches. It was found that the results of the proposed theory had acceptable compliance with the numerical simulation.